2016
DOI: 10.1038/ncomms12073
|View full text |Cite
|
Sign up to set email alerts
|

The ER membrane-anchored ubiquitin ligase Hrd1 is a positive regulator of T-cell immunity

Abstract: Identification of positive regulators of T-cell immunity induced during autoimmune diseases is critical for developing novel therapies. The endoplasmic reticulum resident ubiquitin ligase Hrd1 has recently emerged as a critical regulator of dendritic cell antigen presentation, but its role in T-cell immunity is unknown. Here we show that genetic deletion of Hrd1 in mice inhibits T-cell proliferation, production of IL-2, and differentiation of Th1 and Th17 cells, and consequently protects mice from experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 48 publications
3
51
0
Order By: Relevance
“…HRD1 floxed mice were used as previously described (Kong et al , ; Xu et al , ; Yang et al , ). Albumin‐Cre (catalogue no.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HRD1 floxed mice were used as previously described (Kong et al , ; Xu et al , ; Yang et al , ). Albumin‐Cre (catalogue no.…”
Section: Methodsmentioning
confidence: 99%
“…The IRE1α downstream transcription factor Xbp‐1 has been shown to regulate HRD1 mRNA transcription, providing an interesting feedback loop for HRD1‐IRE1α during ER stress response (Gao et al , ). We recently found that HRD1 is involved in immune regulation in dendritic cell antigen presentation, as well as in the activation of both T and B lymphocytes (Kong et al , ; Xu et al , ; Yang et al , ). However, it is not clear whether HRD1 is regulated upon metabolic stresses.…”
Section: Introductionmentioning
confidence: 99%
“…In Gimap5 null hosts, which have spontaneous apoptosis in T cells, knocking down of CHOP inhibited T cell apoptosis [45]. In addition, a recent study revealed that deletion of Hrd1, an E3 ligase involved in UPR-induced ERAD, led to reduced T cell numbers and attenuated T cell polarization into Th1, Th2 and Th17 [46]. Therefore, moderate UPR promoted T cell function, whereas overwhelming UPR signaling will lead to impaired T cell responses and cell death.…”
Section: The Role Of Upr In T Cells Under Physiological and Pathologimentioning
confidence: 99%
“…Increased XBP-1 splicing, but not PERK or ATF6 activation, along with high expression of BiP and CHOP were found in acute necrotizing enterocolitis (A-NEC) patients who also had lower Th17 and Treg numbers [47]. In the experimental autoimmune encephalomyelitis (EAE) model, downregulating UPR via weakening ERAD leads to low disease progress, indicating that targeting UPR pathways may be a promising therapeutic option for multiple sclerosis [46]. Currently, whether UPR regulates T cell viability and function in the TME remains mostly elusive.…”
Section: The Role Of Upr In T Cells Under Physiological and Pathologimentioning
confidence: 99%
“…Mice have been backcrossed onto the C57/BL6 genetic background for 7 generations. T cell-specific Gcn5- null mice were generated by breeding Gcn5 floxed mice with Lck-Cre transgenic mice as reported (23). Gcn5 loxp/loxp UB/ESR-Cre TG mice were generated by breeding Gcn5 floxed mice with UB / ESR-Cre transgenic mice.…”
Section: Methodsmentioning
confidence: 99%